Food-derived peptides with inhibitory capacity for HMG-CoA reductase activity: a potential nutraceutical for hypercholesterolemia - Guillermo Santos-Sánchez; Ana Isabel Álvarez-López; Eduardo Ponce-España; Patricia Judith Lardone; Antonio Carrillo-Vico; Ivan Cruz-Chamorro (Food Science and Human Wellness)
Cardiovascular diseases (CVDs) are the leading global cause of mortality and disease burden. Statins are the most prescribed lipid-lowering drugs to treat hypercholesterolemia and prevent CVDs. The biochemical mechanism of statins consists of competitive inhibition of the 3-hydroxy-3-methylglutaryl-coenzyme A reductase enzyme (HMG-CoAR), the limiting enzyme in cholesterol biosynthesis. Due to statin intolerance in some patient groups, the search for new inhibitors is a field of great interest. This review focusses on the studies reporting the inhibitory effect of protein hydrolysates and biopeptides on the HMG-CoAR enzyme activity. The analysis of the action mechanism and physicochemical characteristics of the HMG-CoAR inhibitory peptides revealed that the molecular weight, amino acid composition, charge, and polarity are key aspects of the interaction with the HMG-CoAR enzyme. In conclusion, this review reveals the potential of using food peptides as new cholesterol-lowering agents and opens a new interesting field of research. However, clinical approaches are mandatory to confirm their therapeutic hypercholesterolemic effect.